Numa the Pythagorean - Wiseman, T. P. (Histos)

(untitled) (University of Alberta Library, 2026)
One of the more puzzling problems in Greco-Roman historiography is the very strong tradition that Numa Pompilius, creator of the Romans’ religious system, was a pupil of Pythagoras, who set up his school in south Italy about 530 bc. The idea was denounced by Cicero and Livy as an anachronistic fiction—but how could it have come to be so widely believed? This article draws attention to the very extensive Pythagorean material reproduced in Plutarch’s life of Numa, and Plutarch’s own reasonable doubts about the accuracy of the received chronology of the Roman kings. The tradition of Numa the Pythagorean evidently predated the creation of the chronology, so why should it be dismissed as unhistorical? An innovating religious legislator at Rome in the late sixth century bc is a hypothesis that deserves to be taken seriously.